2015
DOI: 10.1093/ckj/sfu140
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for preserving residual renal function in peritoneal dialysis patients

Abstract: Although there have been many advancements in the treatment of patients with chronic kidney disease (CKD) over the last 50 years, in terms of reducing cardiovascular risk, mortality remains unacceptably high, particularly for those patients who progress to stage 5 CKD and initiate dialysis (CKD5d). As mortality risk increases exponentially with progressive CKD stage, the question arises as to whether preservation of residual renal function once dialysis has been initiated can reduce mortality risk. Observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 107 publications
2
33
0
1
Order By: Relevance
“…Our results are in keeping with previous smaller single centre reports, suggesting that younger healthier dialysis patients are more likely to self-report depressive symptoms, whereas older more co-morbid patients report fewer symptoms [23,25]. We also found an association with diabetes and increasing BDI-II score, this may be because both dialysis and diabetes impose restrictions on dietary intake, and on one hand dialysis impacts on diabetic control, and on the other residual renal function is often more rapidly lost with diabetic kidney disease [26]. Although an increased CRP was retained in the model, CRP was not a significant independent factor.…”
Section: Discussionsupporting
confidence: 59%
“…Our results are in keeping with previous smaller single centre reports, suggesting that younger healthier dialysis patients are more likely to self-report depressive symptoms, whereas older more co-morbid patients report fewer symptoms [23,25]. We also found an association with diabetes and increasing BDI-II score, this may be because both dialysis and diabetes impose restrictions on dietary intake, and on one hand dialysis impacts on diabetic control, and on the other residual renal function is often more rapidly lost with diabetic kidney disease [26]. Although an increased CRP was retained in the model, CRP was not a significant independent factor.…”
Section: Discussionsupporting
confidence: 59%
“…Because body fluid control is mainly influenced by RRF, the decline of RRF causes poor body fluid control in PD patients. Moreover, many studies have demonstrated that preserving RRF is associated with improved survival in PD patients [6]. Urine volume is a useful indicator of RRF, and a decline in urine volume suggests a decrease in RRF [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, preserving RRF is particularly important for patients on PD. For the purpose of RRF preservation, some strategies have been reported effective [66]. These include keeping proper body fluid volume and controlling BP.…”
Section: Considerations For Residual Renal Function and Peritoneal Fumentioning
confidence: 99%